Development of EST‐SSR markers in Saxifraga sinomontana (Saxifragaceae) and cross‐amplification in three related species. (12th June 2019) - Li, Yan; Jia, Liu‐Kun; Zhang, Fa‐Qi; Wang, Zhi‐Hua; Chen, Shi‐Long; Gao, Qing‐Bo
Abstract : Premise: Saxifraga sinomontana (Saxifragaceae) is a widespread alpine species in the Qinghai–Tibetan Plateau and its flanking mountains. We developed a set of expressed sequence tag–simple sequence repeat (EST‐SSR) markers to investigate the genetic diversity and evolutionary history of the species. Methods and Results: We initially designed 50 EST‐SSR markers based on transcriptome data of S. sinomontana . Nineteen of 50 loci (38%) were successfully amplified, 13 of which were polymorphic. These were tested on 71 individuals from four populations. Three to 18 alleles per locus were detected, and the levels of observed and expected heterozygosity ranged from 0.2817 to 0.9155 and 0.2585 to 0.8495, respectively. In addition, cross‐amplification was successful for all 13 loci in three congeneric species, S. tangutica, S. heleonastes, and S. congestiflora . Conclusions: These EST‐SSR markers will be useful for studying the genetic diversity of S. sinomontana and disentangling the phylogenetic relationships of related species.